Ethanol production from fermentation of sago starch - Dayang Salwani, Awang Adeni. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Hydrolyzed sago starch (HSS) which acts as a substrate for the production of the ethanol was studied in a fermentation process by Zymomonas mobilis AT 10988. The study was carried out in three stages, namely, enzymatically hydrolysis, batch and continuous fermentation studies. From the hydrolysis studies, a 20% (w/v) sago starch concentration resulted in the highest conversion (98.64%) to reducing sugar compared to other starch concentrations. Optimum enzyme concentration for hydrolysis were 0.5 ul/g and 0.6 ul/g for Termamyl 120L and Dextrozyme. Liquefacstion and saccharification process was conduced at pH 6.5 and pH4.5 respectively, with the incubation period for liquefaction was 2 hours. Studies using batch culture system employing various concentrations of commercial glucose showed that glucose with 10% concentration was able to produce 35.70% g/L ethanol with fermentation efficiency of 86.95%, better than other glucose concentrations (15%, 20% and 25%).